A manifestação dos obstáculos epistemológicos nas dinâmicas das aulas de matemática da educação de jovens e adultos (EJA) - Paula, Maurício de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This work aimed to identify what, in the classroom dynamics of the EJA (Youngster and Adult Education) classroom, manifests itself as an epistemological obstacle to mathematical knowledge. For this, we base our studies in the literature, mainly in the work of Gaston Bachelard (1938), so that we understand what these epistemological obstacles. We also turn to scientific articles and official documents to understand how the Education of Youngster and Adults is and how are Education Mathematics of Youngster and Adults. The theoretical exploration gave us subsidies for, in a phenomenological posture, to accompany the mathematics class of the EJA. We experience the situations proposed by the teacher, we record classes and, in transcribing this experience, we organize the significant scenes. In a movement of analysis they were perceived convergences and divergences that allowed the constitution of open categories. We name them learning math in EJA and teaching math in EJA. From the discussion of what in these categories was relevant to the understanding of the discussion we understand that there are several obstacles to mathematical learning that manifest themselves in different ways, and should be the object of teacher attention

Este trabalho tem como objetivo identificar o que, nas dinâmicas da sala de aula da Educação de Jovens e Adultos (EJA), se manifesta como obstáculo epistemológico ao conhecimento matemático. Para isso baseamos nossos estudos na literatura, principalmente na obra de Gaston Bachelard (1938), que nos permite entender o que são os obstáculos epistemológicos. Voltamo-nos, também, para artigos científicos e documentos oficiais buscando compreender como é a Educação de Jovens e Adultos e como é a Educação Matemática de Jovens e Adultos. A exploração teórica nos deu subsídios para, em uma postura fenomenológica, acompanhar as aulas de matemática da EJA. Vivenciamos as situações propostas pelo professor, fizemos registros de aulas e, ao transcrever essa experiência, organizamos as cenas significativas. Num movimento de análise foram sendo percebidas convergências e divergências que possibilitou a constituição de categorias abertas. As nomeamos o aprender matemática na EJA e o ensinar matemática na EJA. A partir da discussão do que nessas categorias era relevante à compreensão do interrogado na pesquisa, expusemos os obstáculos epistemológicos que vimos emergir na sala de aula. Finalizando a discussão entendemos que, há variados obstáculos à aprendizagem matemática que se manifestam de diversas formas, devendo ser objeto de atenção do professor
The manifestation of the epistemological obstacles in the dynamics of the mathematics classes of the education of youngster and adults (EJA)
Keywords: Matemática - Estudo e ensino; Epistemologia; Educação de adultos; Mathematics Study and teaching